Analytical methods for investigating in vivo fate of nanoliposomes: A review - Chong Su; Yingze Liu; Yang He; Jingkai Gu (Elsevier, 2018)
Nanoliposomes are considered to be the most successful nanoparticle drug delivery system, but their fate in vivo has not been fully understood due to lack of reliable bioanalytical methods, which seriously limits the development of liposomal drugs. Hence, an overview of currently used bioanalytical methods is imperative to lay the groundwork for the need of developing a bioanalytical method for liposome measurements in vivo. Currently, major analytical methods for nanoliposomes measurement in vivo include fluorescence labeling, radiolabeling, magnetic resonance imaging (MRI), mass spectrometry and computed tomography. In this review, these bioanalytical methods are summarized, and the advantages and disadvantages of each are discussed. We provide insights into the applicability and limitations of these analytical methods in the application of nanoliposomes measurement in vivo, and highlight the recent development of instrumental analysis techniques. The review is devoted to providing a comprehensive overview of the investigation of nanoliposomes design and associated fate in vivo, promoting the development of bioanalytical techniques for nanoliposomes measurement, and understanding the pharmacokinetic behavior, effectiveness and potential toxicity of nanoliposomes in vivo. Keywords: Liposomes, Analytical methods, In vivo fate, Liposomal drug